Making a living while making a difference : conscious careers for an era of interdependence - Everett, Melissa (New Society Publishers, 2007)
Making a Living While Making a Difference is a timely and highly informative guide to a working life built on principled choices and an entrepreneurial attitude. It's about greener enterprises and technologies, socially responsible business, innovative nonprofit work, and reinventing government. It's really about putting the pieces together with creativity and hope.